PENGEMBANGAN MATERI TEKS EKSPLANASI BERBANTUAN APLIKASI CAPCUT VIDEO EDITING DI KELAS XI IPS 1 SMA NEGERI 1 KUTABULUH KABUPATEN KARO - Juan Markus Perangin-angin (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2022)
The purpose of this study was to determine the process of developing explanatory text material based on CapCut Video Editing media in class XI SMA and to determine the feasibility of the product produced using the CapCut Video Editing application for explanatory text material in class XI SMA. This study uses research and development methods using the Borg and Gall procedure with the stages of needs and problem analysis, product design, product development, product validation, and product revision. The calculation of the feasibility value was determined using a Likert scale on the validation results of material experts and media experts. The results showed that the product resulting from the research "Development of Explanatory Text Materials Based on CapCut Video Editing Media in Class XI SMA" was included in the "very good" category. This is based on the results of material expert validation conducted twice with a score of 93% in the "very good" category and 2 times media expert validation with a score of 94% in the "very good" category. Thus, the product is said to be suitable for use in the learning process